Non-Moufang variety of Steiner loops satisfying Moufang's theorem. Issue 5 (4th May 2021) - Rasskazova, Marina
Abstract: We construct a non-Moufang variety of Steiner loops H such that every loop from H satisfies Moufang's theorem. This example solves Rajah's problem on the existence of such varieties.